Caracterização morfológica de variedades crioulas de abóboras (Cucurbita maxima) do sul do Brasil - Priori, Daniela; Barbieri, Rosa Lía; Mistura, Claudete Clarice; Castelo Branco Villela, Juliana (Revista Ceres, 2025)
The objective of this work was to morphologically characterize Cucurbita maxima landraces. Nine landraces were characterized by seven quantitative descriptors and 13 qualitative descriptors. The seeds were cultivated in black polystyrene bags filled with substrate in greenhouse. When the plants had at least two definitive leaves, 20 seedlings of each landrace were transplanted to the experimental field, spaced 2.5 m between plants and 4 m between rows, in a completely randomized design. Quantitative data were subjected to analysis of variance. Tukey test was used for the comparison of means, using the SAS 9.2 program. Data of quantitative traits were subjected to the principal component analysis, using the R program. For the qualitative traits, the characterization was expressed by the mode of each accession for each descriptor. Qualitative traits were analyzed as multicategorical variables. Similarity matrix was generated in the GENES program, and a dendrogram was constructed by the UPGMA method using the NTSYS program. Genetic variability was evidenced for the quantitative and qualitative traits evaluated. The analysis of variance showed significant differences between the means. Weight, shape, fruit color, bark thickness, and number of seeds per fruit are relevant characters to indicate promising landraces for breeding, with potential for use as sources of genes and development of cultivars.